Підвищення мотивації студентів в умовах дистанційного навчання. - Бешлей, Ольга; Орищук, Сергій (My University, 2021)
The article examines ways of increasing undergraduate students’ motivation in a distance learning environment. The research was carried out at Chernivtsi National University in the Department of English. In times of the pandemic Covid-19 distance learning mode has become the basis of the modern educational process. Universities face new challenges with regard to the implementation of educational technologies into everyday learning. Modern ICT expand access to various types of information, promote knowledge acquisition, more effective assessment tools and virtual classroom management. The main emphasis is placed on the potential of using the latest distance learning technologies and educational platforms in foreign language teaching to maintain and build students’ motivation to study efficiently in a distance learning environment. However, teaching academic disciplines in the distance learning format requires a more considered approach in defining learning outcomes, as well as in designing qualitatively new methodological materials. The purpose of the study is to investigate students’ learning needs, and, in particular, to find viable ways of motivating them, taking into account the lack of authentic interaction with their peers and the lecturer. The scientific novelty of the study is the analysis of online learning tools used in a distance learning environment as a means of increasing student motivation. Drawing on the importance of the lecturer’s role in the educational process, we suggested a model of professional activity compatible with the current learning and teaching conditions. The results of the conducted surveys and interviews reflected the main difficulties and obstacles faced by the students. Further research can be done in the area of assessing university students’ learning outcomes in a distance learning environment
Keywords: distance learning, the English language, educational space, synchronous and asynchronous learning, educational Internet platforms, foreign (English) language, increasing students’ motivation, flexibility.